The Contingency of Process, or Why There Is No Computation-in-itself - Mark B. N. Hansen (Media Theory, 2024)
This text responds to Alan Díaz Alva’s careful and compelling account of the tensions between and ultimate compatibility of Beatrice Fazi’s work on the formal incomputability of computation and my account of computational media in Feed-Forward. I recount Díaz Alva’s reconstruction of the “claim for inversion” I introduce in my book and suggest that the priority it grants the “superject” over the concrescing subject means that all process is both self- and other-determined. Linking this double determination to Whitehead’s insistence on the basal “dipolarity” of process according to which all prehension involves both physical and conceptual feelings, I question what Díaz Alva felicitously dubs Fazi’s “minimal definition of computation as self-determination.” Linking it to Fazi’s effort to isolate the conceptual-formal dimension of computation from its physical-sensible dimension, I try to show that this limitation of computation to self-determination provides the ground for Fazi’s effort to conceptualize computability and the incomputable on the basis of an internal contingency that is purely formal. I suggest that this effort is in fact what Whitehead would call an “abstraction,” which is to say, an empirical experience of “preanalytical,” in-itself unknowable process. Treating it as abstraction allows us to discern the operation of a more basal contingency – an intrinsic contingency – that lies at the core of all process and that is the source for the formalist abstraction (and all other possible abstractions). Returning to Díaz Alva’s generous proposal regarding our respective projects, I conclude that our accounts can indeed be made compatible although on slightly different terms than the ones Díaz Alva outlines. To that end, I introduce an account of the incomputable rooted in the excess of the sensible over computational measurement (Giuseppe Longo) and offer a concrete proposal for how to incorporate the formal dimension (pure potentiality) of computation into the concreteness of process.